Genetic Variation and Assessment of Seven Salt-Tolerance Genes in an Indica/Xian Rice Population - Yuanhang Cheng; Tao Wang; Yeying Wen; Xingfei Zheng; Haifeng Liu; Xiangsong Chen; Ying Diao; Zhongli Hu; Wenjie Feng; Zhaohui Chu (Agronomy)
Natural variations conferring salt tolerance (ST) are of great value for breeding salt-tolerant rice varieties. The major ST genes, including SKC1, RST1, OsWRKY53 and STG5, have been identified to contain or be associated with a specific single nucleotide polymorphism (SNP). However, the distribution and genetic effects of those ST genes in rice cultivars remain poorly understood. Here, we investigated the distribution of seven cloned ST genes, including SKC1 (P140A, R184H), RST1 (A530G, E611G), OsWRKY53 (A173G), STG5 (I12S), OsHKT1;1 (L94K), OsHKT2;3 (I77T) and OsSTL1 (P289S), which contain one or two ST-related SNPs in a sequenced Indica/Xian rice population comprising 550 accessions. On the basis of the SNPs, the population was categorized into 21 haplotypes (Haps), each of which contained at least four out of seven ST genes. To precisely evaluate each SNP, grouped rice varieties that only differed at one SNP were chosen from two Haps for salt treatment with 150 mM NaCl for 7 d. The results revealed that RST1611G showed up to 88.6% improvement in salt tolerance considering the relative shoot fresh weight (rSFW). Alternatively, OsWRKY53173G, OsHKT2;377T, SKC1140A and SKC1184H showed an improvement in rSFW of 38.6%, 37%, 27.5% and 19.0%, respectively, indicating that they contribute different genetic effects for ST. OsHKT1;194K showed no function with salt treatment for 7 d, but showed a 37.9% rSFW improvement with salt treatment for 14 d. Furthermore, we found that the expression of OsWRKY53173G was positively correlated with SKC1 and conditionally participated in ST dependent on SKC1140A. Interestingly, RST1530A was previously reported to be associated with salt sensitivity, but it was found to be associated with salt tolerance in this study. Overall, our results provide further insight into the mechanism and marker-assisted selection improvement of ST in Indica/Xian rice.